Efektivitas Penerapan Sistem Absensi Online dalam Meningkatkan Disiplin Kerja Aparatur Sipil Negara di Dinas Satpol PP Kabupaten Gresik - Reza Vergiawan; Kriswibowo, Arimurti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The implementation of the online attendance system in the Gresik Regency Regional Apparatus Organization (OPD) faces a number of obstacles, especially related to the use of a fake Global Positioning System (GPS), which can allow manipulation of performance and attendance data. This research aims to determine the effectiveness of the online attendance system in improving the work discipline of State Civil Apparatus (ASN) in the Gresik Regency Civil Service Police Unit Service. The research method used is descriptive qualitative using primary and secondary data. Data collection was carried out through interviews, observation and documentation. The concept of effectiveness in this research is measured by four indicators according to Tangkilisan (2005:141), namely, target achievement, adaptability, job satisfaction, and responsibility. The research results show that despite initially facing obstacles, the implementation of the online attendance system succeeded in increasing employee discipline and performance. This system provides motivation for employees to be more disciplined in attendance and performance reporting, with increased productivity and providing rewards in the form of Additional Income Allowances (TPP) as a significant positive impact. However, it was found that some employees experienced problems in their ability to adapt, such as delays due to slow network operators, causing errors in the application. Nevertheless, the implementation of the online attendance system still makes a positive contribution to increasing work efficiency and discipline in the Gresik Regency OPD environment.